A Structural Equation Model of the Relationship Between Symptom Burden, Psychological Resilience, Coping Styles, Social Support, and Psychological Distress in Elderly Patients With Acute Exacerbation Chronic Obstructive Pulmonary Disease in China - Mengfei Lan; Li Yang; Hongqiang Zhang; Aihua Su; Qiling Yin; Jiaoyue Li (Elsevier, 2024)
Summary: Purpose: The prevalence of psychological distress is frequently observed among old adults with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). However, current researches are insufficient to clarify the correlation among these relevant factors. This study examined the effects of symptom burden, psychological resilience, coping styles, and social support on psychological distress. Methods: Two hundred fifty five elderly patients with AECOPD were conveniently selected in Taian, Shandong Province. The General Information Questionnaire, Distress Thermometer, The Revised Memorial Symptom Assessment Scale, Connor-Davidson Resilience Scale, Simplified Coping Style Questionnaire, Perceived Social Support Scale were used to investigate. The relationship among factors was estimated by using a structural equation model. Results: Psychological distress score of elderly patients with AECOPD was (5.25 ± 1.01); coping styles, psychological resilience, symptom burden, and social support directly affected psychological distress (the direct effects were −.93, .17, .17, and −.09); coping styles had the largest total effect on psychological distress (the total effect was −.93); psychological resilience indirectly affected psychological distress through coping styles (the indirect effect was −.74); symptom burden indirectly affected psychological distress through psychological resilience (the indirect effect was .25); social support indirectly affected psychological distress through symptom burden, psychological resilience, and coping styles (the indirect effect was −.80). Conclusion: The psychological distress of elderly patients with AECOPD is at a moderate level; coping styles, psychological resilience, and social support have positive effects on alleviating the psychological distress of elderly patients with AECOPD; symptom burden is negatively correlated with psychological distress. Healthcare professionals should pay more attention to elderly patients with AECOPD who are particularly prone to experience higher levels of psychological distress, especially in the presence of low coping style, limited psychological resilience, inadequate levels of social support, and high symptom burden.